Morphology and histology of skin (Texas Journal of Medical Science, 2023)
The article presents lecture material on the study of the morphological and functional characteristics of the skin and its derivatives, which are included in the modern range of active and interactive forms of teaching histology in order to effectively form the professional competence of future doctors in the specialties "General Medicine", "Pediatrics" and "Stomatology", as well as students of biological sciences faculties.